Mitral regurgitation increases readmission due to heart failure after percutaneous coronary intervention among patients with ST-elevation myocardial infarction: a retrospective data review. (3rd October 2022) - Alkhalaila, O; Rahhal, A; Abdelghani, M S; Altermanini, M; Habib, M B; Alkhateeb, M H; Hailan, Y; Barakat, M; Shehadeh, M; Shunnar, K; Al-Hijji, M; Arabi, A R
Abstract: Introduction: Post-ST elevation myocardial infarction (STEMI) course can be complicated with mitral regurgitation (MR) which has significant impact on in-patient outcomes and post-discharge course. MR in the setting of STEMI can be due to left ventricular dilatation, papillary muscle rupture or chordal rupture. Purpose: In this retrospective study, we aimed to evaluate the impact of MR on readmission within one year after percutaneous coronary intervention (PCI) in STEMI patients. Methods: We conducted a single-center retrospective observation cohort study. We included all patients admitted to the hospital with diagnosis of STEMI, underwent PCI during the same admission (index admission) and discharged alive in the period between Jan 1st, 2016 and Sep 30th, 2018. Factors associated with readmission due to heart failure within 1 year of discharge were evaluated using multivariate logistic regression and results were reported as odds ratio (OR) with p-value <0.05 indicating statistical significance. Results: A total of 1257 patients were included in our retrospective analysis. The mean age of the study population was 51±10 years. Around 16% (n=206) of the study population had mitral regurgitation (MR) during their admission for STEMI. Among them, 195 patients had newly discovered MR. MR severity was mild in 196 (95%) patients with MR. Unplanned readmission due to cardiac reasons within 1 year of discharge occurred in 103 (8.2%) patients. Among them, 37 (3%) were readmitted due to heart failure. MR was found to increase the likelihood of readmission due to heart failure within one year after PCI among patients with STEMI by three times (aOR=3.13, 95% CI 1.39–7.03; p-value 0.006). As demonstrated in table 1, other positive predictors for readmission due to heart failure were female gender (aOR=3.80, 95% CI 1.22–11.86; p-value 0.021), chronic kidney disease (aOR=4.56, 95% CI 1.22–17.03; p-value 0.024), and clinical heart failure during the index admission (aOR=4.82, 95% CI 1.53–15.15; p-value 0.007). Interestingly, reduced left ventricular ejection fraction was not a significant predictor of heart failure readmission. Conclusion: Mitral regurgitation is relatively common in STEMI and most frequently presents with mild severity. In our study, MR was found to be a strong predictor for readmission due to heart failure within one year after PCI among patients with STEMI, which may warrant frequent follow-up for these patients and proper initiation of and titration of guideline-directed medical therapy (GDMT). Funding Acknowledgement: Type of funding sources: None.